Implementation of Law No. 17 of 2023 on Dispute Resolution between Patients and Health Workers in Complications of Eye Surgery - M. Ammar Al Ghifari; Irsyam Risdawati; Muhammad Arif Sahlepi (Journal Evidence Of Law, 2026)
Medical complications, particularly in eye surgery, are inherent risks that may lead to disputes between patients and healthcare providers. In Indonesia, Law Number 17 of 2023 and Government Regulation Number 28 of 2024 emphasize non-litigation mechanisms, especially mediation, as the primary approach to resolving medical disputes. This framework aims to protect both parties while reducing the burden of litigation. This study analyzes the implementation of these regulations in resolving disputes arising from ophthalmic surgical complications, focusing on legal certainty, justice, and balanced protection.This research employs a normative legal method using statutory and literature approaches. The analyzed regulations include Law Number 17 of 2023, Law Number 29 of 2004, Law Number 36 of 2009, Law Number 30 of 1999, and Supreme Court Regulation Number 1 of 2016. Secondary data from textbooks, journals, case reports, and court decisions were examined using qualitative descriptive analysis.The findings indicate that mediation serves as a mandatory initial step in resolving medical disputes. Non-litigation pathways are considered faster, more cost-effective, and less confrontational than litigation. Professional disciplinary bodies play a crucial role in assessing alleged negligence proportionally. Legal protection for healthcare providers is ensured without neglecting patients’ rights. Overall, the regulation strengthens a restorative justice approach, maintains the therapeutic relationship, and balances rights and obligations, although challenges remain in technical implementation and public awareness.